ANALISIS PENATAAN REGULASI INVESTASI DI INDONESIA MELALUI UNDANG-UNDANG OMNIBUS LAW UNTUK MENJAMIN KEPASTIAN HUKUM - Saputri, Alfiyana; Ushsholikhah, Iva; Munawaroh, Rizka Khoridatul; Rismaeni, Raisya Erta (LPPM Universitas Bina Bangsa, 2025)
Investment regulations in Indonesia often face the challenge of disharmony and overlap between regulations, which results in legal uncertainty and hampers investment flows. This study aims to evaluate the impact of implementation of the Omnibus Law on legal certainty in investment within Indonesia. The methodology employed is normative legal research with a focus on statutory regulations, utilizing secondary data obtained from existing literature. The research results show that the Omnibus Law simplifies various regulations related to investment, improves bureaucracy, and reduces conflicts between regulations. However, its implementation still raises controversy, including the potential for neglecting the protection of workers' rights and the environment, as well as conflicts with old regulations. Based on the theory of legal certainty, the application of the Omnibus Law can provide legal clarity and stability that supports the investment climate. Clear and integrated regulations are an important factor in attracting the interest of domestic and foreign investors. The research conclusion states that structuring regulations through the Omnibus Law provides significant opportunities to increase investment in Indonesia, but must be balanced with effective supervision so that implementation does not violate the principles of justice and legal protection. Therefore, the Omnibus Law has the potential to serve as a longterm solution for national economic development, provide that the challenges in its execution implementation can be addressed.